1994
DOI: 10.1002/eji.1830240119
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of interleukin‐6 receptors by interleukin‐6 and interferons in multiple myeloma cell lines

Abstract: Interleukin-6 (IL-6) mediates pleiotropic functions through specific receptors (IL-6R) composed of an 80-kDa binding protein, associated with a non-ligand binding protein (gp130) which transduces the signal. Because IL-6 is the major tumor growth factor in multiple myeloma, we investigated the regulation of IL-6R in two human multiple myeloma cell lines. Binding experiments with 125I-labeled IL-6 showed that IL-6R were expressed at a high density on RPMI-8226 cells (15 000 receptors/cell), but no specific bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
(15 reference statements)
3
7
0
Order By: Relevance
“…4 B) and myeloid U937 cells ( Fig. 6 C); similar observations were made by Lasfar et al (49). Importantly, these investigators also reported IFN-a-mediated gp8O down-regulation on another IL-6-dependent myeloma cell line (XG-l) and, similarly, IFN-a-mediated gp8O up-regulation on another IL-6-independent myeloma cells (RPMI-8226).…”
Section: Resultssupporting
confidence: 84%
“…4 B) and myeloid U937 cells ( Fig. 6 C); similar observations were made by Lasfar et al (49). Importantly, these investigators also reported IFN-a-mediated gp8O down-regulation on another IL-6-dependent myeloma cell line (XG-l) and, similarly, IFN-a-mediated gp8O up-regulation on another IL-6-independent myeloma cells (RPMI-8226).…”
Section: Resultssupporting
confidence: 84%
“…Despite the apparent involvement of IL-6 in the growth of MM5.1 cells, we failed to demonstrate a significant expression of the IL-6 receptor (gp80) on the surface of the cells when they were cocultured with bone marrow stroma. This observation is consistent with the finding of Lasfar et al 33 who found a down-regulation of membrane IL-6 receptors on the myeloma cell line XG1 in the presence of IL-6, although this line is completely IL-6 dependent for its growth. This may indicate that a low number of surface gp80 molecules (even under the detection limit in FACS analysis) might be sufficient to mediate IL-6 signal transduction.…”
supporting
confidence: 93%
“…The bioactivity was more enhanced when hIL-6 and its analogs were acting through soluble rather than membrane-bound forms of hIL-6Ra, and when the shIL-6Ra concentration was kept below or around the physiological levels present in human sera. Indeed, hIL-6 has been shown to down-regulate the surface expression of hIL-6Ra in A375 (Schwabe et al, 1994) and XG-1 (Lasfar et al, 1994) cells, probably as a consequence of a ligand-dependent increase in the internalization rate (Dittrich et al, 1994). Although we cannot exclude that selected high affinity mutants bind the soluble form of hIL-6Ra more tightly than the cellular form, we rather favor the idea that receptor clustering on the surface of cytokine-stimulated cells increases the local concentration of hIL-6Ra to levels well above the KD of the superbinders.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it cannot be excluded that the maximum bioactivity attainable is limited by the faster internalization rate of the membrane-bound versus the soluble hIL-6Rc. Indeed, hIL-6 has been shown to down-regulate the surface expression of hIL-6Ra in A375 (Schwabe et al, 1994) and XG-1 (Lasfar et al, 1994) cells, probably as a consequence of a ligand-dependent increase in the internalization rate (Dittrich et al, 1994). Potential advantages of hlL-6 high affinity variants Several studies have proposed hIL-6 as a thrombopoietic, as well as an anticancer agent, due to well defined effects on hIL-6Ra-bearing cells (Akira et al, 1993).…”
Section: Shil-6ra-dependent Superagonistic Activity Of Hil-6 High Affmentioning
confidence: 99%